PENGARUH KADAR DEBU AMBIEN TERHADAP GANGGUAN KAPASITAS FUNGSI PARU : STUDI KOMFERATIF ANTAR PEKERJA PADA PT JR DAN PT SR - Gusman Virgo; Sukendi Sukendi; Zulkarnaini Zulkarnaini (Program Pascasarjana Universitas Riau, 2016)
Lung capacity is the capacity of lung function that is the description of the function of the respiratory system ventilation so that an unknown amount of capacity ventilation and the presence or absence of lung function abnormalities ventiliator (Brunner & Suddarth, 2010). Process disturbance lung capacity at the start of their lung function disorders caused by the presence of dust. Dust is one of the pollutants that can lead to respiratory problems for workers in industries associated with the dust in the production process. Dust is also often referred to as particles suspended in air (Suspended Particulate Metter / SPM) with a size of 1 micron to 500 microns. The purpose of this study was to determine the analysis comparison of ambient dust levels on the incidence of lung disorders vital capacity in industrial factory workers. This study uses observational study design, with a cross-sectional design that was conducted in June-August 2015 in Plant PT JR and SR Kampar PT. Number of samples 40 people. Measuring instruments used are questionnaires and observation sheets. Analiais data used is simple logistic regression. The results showed that the density of dust is not normal in a company 10 times the risk of impaired lung function compared to the density of dust in the normal threshold (CI 2.892 to 21.659). While the company at risk of 21.6 times and impaired lung function compared to the density of dust in the normal threshold (CI 1.313 to 335.951) after controlling for confounding variables is the variable sport. Workers who are not using PPE at company A risk 8 times impaired lung function compared with workers who use PPE (CI 2.692 to 24.659). While the company and 3.5 times the risk of impaired lung function compared with workers who use PPE (CI 0.166 to 73.717). Advised on factory workers to maintain the safety of health themselves by using personal protective mill dust density environment experienced during work.